2016
DOI: 10.1002/cssc.201501593
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Oxidation of Carbohydrates in an Efficient Electrochemical Energy Converter: Cogenerating Organic Electrosynthesis

Abstract: The selective electrochemical conversion of highly functionalized organic molecules into electricity, heat, and added-value chemicals for fine chemistry requires the development of highly selective, durable, and low-cost catalysts. Here, we propose an approach to make catalysts that can convert carbohydrates into chemicals selectively and produce electrical power and recoverable heat. A 100% Faradaic yield was achieved for the selective oxidation of the anomeric carbon of glucose and its related carbohydrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
96
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(101 citation statements)
references
References 74 publications
4
96
0
1
Order By: Relevance
“…12,25 We reported the use of "Bromide Anion Exchange" (BAE) method, [29][30][31] a surfactant-free approach, to develop a line-up of Au-Pd-Pt nanocatalysts able to oxidize efficiently glucose at low electrode potentials at various pHs. [32][33][34] It was also shown that monometallic Au enables a selective oxidation of a range of carbohydrates by their anomeric position and even in a cogeneration fuel cell; 13,35 however, it was postulated that the selectivity remained limited to Au that exhibits remarkable catalytic activity [36][37][38] toward aldehydes and hemiacetals oxidation. Herein, we examine the extended analysis on Au 100-x M x (M = Pd, Pt) catalysts by coupling electrochemical techniques with spectroscopic and chromatographic methods to unravel the outstanding ability of these electrocatalysts, enabling the acquisition of clear and precise information on the electrocatalytic reaction.…”
Section: H426mentioning
confidence: 99%
See 4 more Smart Citations
“…12,25 We reported the use of "Bromide Anion Exchange" (BAE) method, [29][30][31] a surfactant-free approach, to develop a line-up of Au-Pd-Pt nanocatalysts able to oxidize efficiently glucose at low electrode potentials at various pHs. [32][33][34] It was also shown that monometallic Au enables a selective oxidation of a range of carbohydrates by their anomeric position and even in a cogeneration fuel cell; 13,35 however, it was postulated that the selectivity remained limited to Au that exhibits remarkable catalytic activity [36][37][38] toward aldehydes and hemiacetals oxidation. Herein, we examine the extended analysis on Au 100-x M x (M = Pd, Pt) catalysts by coupling electrochemical techniques with spectroscopic and chromatographic methods to unravel the outstanding ability of these electrocatalysts, enabling the acquisition of clear and precise information on the electrocatalytic reaction.…”
Section: H426mentioning
confidence: 99%
“…New type of devices so-called "co-generation or co-production" FCs arise from the possibility of reaching efficiently and simultaneously these two goals. 8,9,[11][12][13][14][15] For instance, the current platforms for H 2 production are largely based on fossil fuels (steam methane reforming, coal gasification), and lead to the emission of significant quantities of greenhouse gases (CO 2 and other carbon-based species in addition to the need of high temperatures), which apparently violates our original intention of reducing global warming by the employment of H 2 power. 16 Besides, the organic electrosynthesis is expected to replace, somehow, toxic or hazardous reagents, avoid large quantities of stoichiometric oxidizers and reducers as well as the in situ production of unstable and/or hazardous chemicals, which means that the waste originating from the used reagents is almost negligible.…”
mentioning
confidence: 99%
See 3 more Smart Citations